2022
DOI: 10.1111/iej.13728
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ethylenediaminetetraacetic acid on regenerative endodontics: A systematic review

Abstract: Background The effects of ethylenediaminetetraacetic acid (EDTA) on regenerative endodontic procedures (REPs) are controversial, because, despite releasing growth factors from dentine, some studies show negative effects on cell behaviour. Objectives The aim of the study was to investigate the influence of the use of EDTA in REP on the growth factors’ release, cell behaviour and tissue regeneration. Methods A systematic search was conducted (PubMed/Medline, Scopus, Cochrane Library, Web of Science, Embase, Open… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 79 publications
(241 reference statements)
0
5
0
1
Order By: Relevance
“…El EDTA es actualmente el solvente entérico más utilizado como enjuague endodóntico en combinación con hipoclorito de sodio 10 . Se considera un agente con propiedades más Marjorie Michelle Guananga-Manobanda; Nadia Fernanda Loja-Ortiz Emma Maricella Arroyo-Lalama 1040 compatibles con su sistema de canales y ambiente biológico.…”
Section: Análisis De Los Resultadosunclassified
“…El EDTA es actualmente el solvente entérico más utilizado como enjuague endodóntico en combinación con hipoclorito de sodio 10 . Se considera un agente con propiedades más Marjorie Michelle Guananga-Manobanda; Nadia Fernanda Loja-Ortiz Emma Maricella Arroyo-Lalama 1040 compatibles con su sistema de canales y ambiente biológico.…”
Section: Análisis De Los Resultadosunclassified
“…A recent systematic review stated that EDTA conditioning has valuable advantages on REP. It promotes tissue neo-formation and speeds up the healing process by increasing dentin transforming growth factor-1 release and improving stem cell migration and differentiation [ 17 ]. Conversely, some research found that EDTA-treated dentin did not affect cell viability [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The dentin proteome has been shown to promote neurite outgrowth [54,55] and to stimulate odontoblast differentiation and/or tertiary dentin secretion [56,57]. These growth factors in dentin can be released from the dentin into the pulp during endodontic treatments [58][59][60][61][62][63] and are being studied for their potential in regenerative endodontics. It is possible that the dentin similarities between our Tgfbr2 cko and WT mice may be masking a differential response that would occur if the proteomes were different.…”
Section: Discussionmentioning
confidence: 99%